Determinan Agresivitas Bank Dalam Pengambilan Risiko: Kasus Indonesia - Simanjuntak, Pittauli Lidia; Wibowo, Buddi (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 13 Nomor 2 Tahun 2019DO - 10.24843/MATRIK:JMBK.2019.v13.i02.p10, 2019)
This study is aimed to identify and analyze the important factors that affect the aggressiveness of bank risk taking in Indonesia. Referring to previous research in several countries, market interest rate, bank capitalization, profitability, bank asset size, bank income diversification and bank efficiency are the influential factors that drives bank risk taking behavior. This study uses Jakarta Interbank Offered Rate, Indonesia Government Bonds Yield, Bank Indonesia Rate, and Bank Level Lending Rate as market interest rate measures. Level of aggressiveness in taking risk is measured by using the amount of risky assets owned by banks and bank credit risk. Credit risk is measured by using loan loss reserves. The results show that Bank Indonesia Rate is the most interest rate affecting bank aggressiveness in risk taking as measured by risk assets and measured by loan loss reserves. Efficiency, income diversification, and profitability are significant factor that affect bank risk taking.